Is Repeat Transurethral Resection Always Needed in High-Grade T1 Bladder Cancer? - Calò, Beppe; Chirico, Marco; Fortunato, Francesca; Sanguedolce, Francesca; Carvalho-Dias, Emanuel; Autorino, Riccardo; Carrieri, Giuseppe; Cormio, Luigi (Frontiers in Oncology, 2019)
Re-staging transurethral resection, the so-called repeat TUR (Re-TUR), is mandatory in case of incomplete first transurethral resection of bladder tumor (TURBT). In completely resected high grade T1 tumors, Re-TUR is recommended but question remains whether it provides advantages in terms of recurrence-free survival (RFS), progression-free survival (PFS), and cancer specific survival (CSS). The present study aimed to determine whether Re-TUR improves such outcomes in patients with completely resected high-grade T1 bladder cancer (BC). We queried our prospectively maintained database to identify patients with completely resected high-grade T1 BC who underwent (Group A) or not (Group B) Re-TUR before starting intravesical instillations of Bacillus Calmette-Guerin (BCG). The impact of Re-TUR as well as of other tested variables on RFS, PFS, and CSS was tested by Kaplan-Meier method and Log-rank testing. A total of 118 patients underwent Re-TUR, which pointed out no BC in 61 (51.7%), NMIBC in 54 (45.8%) and pT2 disease in 3 (2.5%). The 3 patients with pT2 disease underwent cystectomy, whereas all others were offered BCG treatment. Forty-two patients refused BCG treatment while 2 did not complete it; therefore, Group A (Re-TUR before BCG treatment) consisted of 71 patients whereas Group B consisted of 40 patients who refused Re-TUR but completed BCG treatment. Mean follow-up was 60 months (range 12-142). Kaplan-Meier curves and Log-rank testing showed no difference in RFS, PFS and CSS between patients who had (Group A) or had not (Group B) Re-TUR before starting BCG treatment. Our findings suggest that a Re-TUR in patients with a completely resected high-grade T1 BC does not translate into a better oncological outcome. Given its impact on both patients and healthcare system, the need for Re-TUR in completely resected high grade T1 BC should be further investigated into the framework of a randomized study.